LEMIERRE'S SYNDROME: A FORGOTTEN COMPLICATION OF OROPHARYNGEAL INFECTION - Shah, Shahid Ali; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2005)
Background: Lemierre's syndrome (postanginal sepsis) usually complicates an oropharyngeal infection as septicemia, septic thrombophlebitis of the internal jugular vein, and metastatic lesions, most frequently in the lungs. Fusobacterium necrophorum is the usual etiologic agent. Lemierre's syndrome is not widely known by clinicians. This study aims at creating awareness amongst the clinicians of existence of this potentially fatal but curable clinical entity. Methods: All the patients admitted in the ENT department of Ayub Teaching Hospital, during the period of January 2000 to December 2002, for the treatment of acute oropharyngeal infection, were critically assessed by consultants, for features of Lemierre's syndrome, and investigated further, accordingly. Results: 156 patients were admitted with acute oropharyngeal infection. Two patients (1.28%) had features suggestive of Lemierre's syndrome. A male and a female, 25 and 28 years old respectively, had a history of a preceding sore throat for a variable duration followed by complications. Attempts were made to make the diagnosis of Lemierre's syndrome and they were treated appropriately, as per recommendations, to a successful outcome. Conclusions: Widespread use of antibiotics for pharyngeal infections has significantly reduced the incidence. Rare and a forgotten complication, Lemierre's syndrome is potentially fatal. Early diagnosis and prolonged treatment with appropriate antibiotics are usually curative. A high degree of clinical suspicion is necessary for diagnosis. Modern day clinician should be aware of this potentially life threatening clinical entity that may complicate a trivial oropharyngeal infection. Keywords: Lemierre's syndrome; Fusobacterium necrophorum; oropharynx; septicemia;